PROYEKSI KEBANGKRUTAN PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA - Anwar Anwar; Nurman; Zainal Ruma; Sitti Hasbiah (Master of Management, Mataram University, 2022)
This study aims to determine financial distress with the Altman Z-score, Zmijewski, and Grover models to predict bankruptcy in LQ45 Index Companies on the Indonesia Stock Exchange. The population of this research is all issuers or publicly listed companies whose shares are consistently included in the LQ45 Index on the Indonesia Stock Exchange for the 2017-2020 period. Sampling using the purposive sampling method. Data collection is done by using documentation techniques. The results of calculations based on the Altman Z-Score model on LQ45 Index companies during the 2017-2021 period obtained eight companies in the gray area and two companies in the distress area, namely PT. XL Axiata Tbk and PT. Jasa Marga (Persero). Meanwhile, using the Zmijewski model, four companies were categorized as experiencing financial distress during the 2017-2020 period, namely PT. Bank Central Asia Tbk, PT. Bank Negara Indonesia (Persero) Tbk, PT. State Savings Bank (Persero) Tbk, PT. Bank Mandiri (Persero) Tbk. Based on the results of the calculation of financial distress with the Grover model, two companies are categorized as experiencing financial distress, namely PT. XL Axiata Tbk and PT. Jasa Marga (Persero). Keywords: Financial Distress, Altman Z-Score, Zmijewski, Grover